2013
DOI: 10.1039/c2lc41264k
|View full text |Cite
|
Sign up to set email alerts
|

An integrated microfluidic cell culture system for high-throughput perfusion three-dimensional cell culture-based assays: effect of cell culture model on the results of chemosensitivity assays

Abstract: Although microfluidic cell culture systems are versatile tools for cellular assays, their use has yet to set in motion an evolutionary shift away from conventional cell culture methods. This situation is mainly due to technical hurdles: the operational barriers to the end-users, the lack of compatible detection schemes capable of reading out the results of a microfluidic-based cellular assay, and the lack of fundamental data to bridge the gap between microfluidic and conventional cell culture models. To addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 36 publications
1
41
1
Order By: Relevance
“…Moreover, it was also found that the generated compressive strain decreased with the increase of operating frequency (Figure 2(b)). At a given pneumatic pressure, the dynamic process to load a pneumatic chamber with an air pressure is time-dependent [28, 29]. Higher operating frequency implies shorter imposition time (e.g., 2.0, 1.0, and 0.5 sec round −1 for the 0.5, 1.0, and 2.0 Hz, resp.)…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was also found that the generated compressive strain decreased with the increase of operating frequency (Figure 2(b)). At a given pneumatic pressure, the dynamic process to load a pneumatic chamber with an air pressure is time-dependent [28, 29]. Higher operating frequency implies shorter imposition time (e.g., 2.0, 1.0, and 0.5 sec round −1 for the 0.5, 1.0, and 2.0 Hz, resp.)…”
Section: Resultsmentioning
confidence: 99%
“…In order to partially address the latter issues, the p3D culture system could also be extended to include the co-culture of a variety of tumor cells with additional, non-transformed cell types such as mesenchymal stromal cells, tumor-associated fibroblasts or endothelial and immunocompetent cells, in order to explore tumor specific microenvironmental features [4]. On the other hand, the use of tumor TLS generated in p3D, eventually produced in miniaturized systems [18,49], properly adapted for the application of direct perfusion, could help to overcome limitations inherent in the use of human cell lines xenografts for drug screening. This could be especially relevant regarding costs, time requirements and confounding effects of murine stromal and innate immune system cells.…”
Section: Discussionmentioning
confidence: 99%
“…By using a heater chip, stable thermal conditions for cell cultivation was provided and non-mechanical pneumatically driven multiplex medium perfusion mechanism (1.6 to 40.7 ll/h) was utilised. 68 For anti-cancer drug screening, Chen et al 52 developed a microfluidic array for 3D cell culture. The device consisted of 32 flow units on a standard 96 well plate where each unit had 3 wells (flow inlet, cell culture chamber, and flow outlet).…”
Section: Integration and Multiplexingmentioning
confidence: 99%